IMPERATIVE SOCIOPRAGMATICS OF THE STP SAHID SURAKARTA’S SPEAKING CLASS - Rifai, Dian (Melekliterasi Press, 2023)
The study aims to describe and analyze the form and meaning of imperative that is used by the English class students at STP Sahid Surakarta when they are practicing speaking skills in the class. The benefit of the research is to increase the insight regarding the form and meaning of imperative students in the classroom dialogue at STP Sahid Surakarta. The study used descriptive qualitative in analyzing the imperative sociopragmatics used by the students. It can be categorized in qualitative research. The researcher used observation and documentation to collect data in this study. The method of presenting and analyzing data is by using a flowchart model. The researcher uses triangulation to determine trustworthiness. This research concludes that there are five imperative forms. Those are the imperative meaning of the invitation in 10 sentences, the imperative meaning of ordering in 9 sentences, the imperative for granting permission in 8 sentences, the imperative for requesting in 7 sentences, and the imperative for prohibition in 6 sentences.